Transformative dynamics of corruptive systems - Rufino, Annamaria (Italian Sociological Review, 2024)
The impact of the global communication system significantly affects the dissemination of corruptive practices, helping to mix truth and falsehood, and confusing the objective interpretation of the dynamics. Corruptive traps get confused with the perception of the emergency. The difficulty of regulatory systems in preventing and correcting the corruption phenomenon contributes to spreading its traps in the social system.